A 6-DOF extended state observer–based adaptive generalized super twisting algorithm of fault-tolerant control for coupled spacecraft with actuator saturation. (May 2023) - Mei, Yafei; Gong, Kejie; Liao, Ying
This paper aims to address an integrated relative attitude and position fault-tolerant control strategy between a follower spacecraft and a leader spacecraft for coupled spacecraft tracking maneuver in the case of inertia parametric uncertainties, external disturbances, actuator failures, and saturation. The coupled rotational and translational kinematics and dynamics of the rigid spacecraft are derived on the Lie group SE(3), where the actuator failures and saturation are taken into account. Then, a 6-DOF extended state observer is proposed by using terminal sliding mode technique to estimate the lumped disturbance in finite time. An adaptive generalized super twisting algorithm of fault-tolerant controller is developed to guarantee the finite-time stability based on the estimated lumped disturbance information. The stability of the closed-loop system is proved in spite of the aforementioned disturbances via the Lyapunov analysis. Finally, the numerical simulation illustrates the effectiveness of the proposed control strategy.